The characteristics and patterns of maxillofacial fractures at Mangusada general hospital, Badung-Bali - Wiwekananda, Agus Bhayu W.; Arimbawa, I Wayan; Roosseno, Ratna Rayeni Natasha (International Journal of Research in Medical Sciences, 2019)
Background: Trauma is one of the leading causes of death among people under 40 years of age and approximately 10 percent of the cases have been maxillofacial trauma. There was limited number of studies on maxillofacial fractures in Indonesia. Thus, this research attempted to investigate the characteristics and patterns of maxillofacial fractures at Mangusada General Hospital in Badung-Bali. Methods: This research was a cross-sectional descriptive study which conducted at Mangusada General Hospital in the period of 1 January 2016 - 31 December 2017. The 127 samples selected using non-probability sampling. The inclusive criteria involved all maxillofacial trauma cases and the exclusive criteria focused on maxillofacial fractures that received intervention or with incomplete medical records. Each data was collected from the medical records and then analysed descriptively. Results: From 127 samples, male dominated the sample on the gender-based criteria (70.1%) and the highest frequency of all age groups is 21-30 years old on the age group based criteria (23.6%). Maxillary fractures are the most occurring maxillofacial cases, which took up 33.6%. The main cause of the cases is traffic accidents (89.0%). Conclusions: Maxillary fractures are the highest maxillofacial cases at Mangusada General Hospital on 1 January 2016 - 31 December 2016 period of time. The productive male age groups are the most affected groups due to traffic accidents.